Implementation of Project-Based Learning Model to Improve Students' Critical Thinking Skills - Endang Komara; Berliana Berliana; Muhammad Firman; Uce Gunawan (Universitas Negeri Semarang, 2023)
Critical thinking skills are essential for students in developing their intellectual skills. Critical thinking involves the ability to objectively analyze, evaluate, and synthesize information. It allows students to make good decisions, recognize strong or weak arguments, and identify weaknesses in their own thinking. Critical thinking skills also help students be critical of information sources, avoid superficial thinking, and face challenges with creative problem solving. In today's information age, critical thinking enables students to become self-reliant, informed, and skilled individuals in the face of the changes and complexities of the modern world. Implementing monotonous learning without considering active student participation is one of the causes of low critical thinking abilities among students. This study aims to enhance students' critical thinking abilities through project-based learning. The research was conducted using a quasi-experimental method. The research design used a nonequivalent pretest-posttest control group design. The study subjects were students from class XI MIA 1 and XI MIA of SMA Negeri 5 Kota Sukabumi and SMAN 1 Sukaraja. The research results, obtained through the t-test, yielded a significance value of 0.007. This means that applied project-based learning can enhance students' critical thinking abilities.